Hepatic focal nodular hyperplasia - Perdomo, Raúl; Pontillo, Mauricio; Massaferro, Gabriel; Rodríguez Temesio, Gustavo (Cirugía del Uruguay, 2020)
Nodular Hyperplasia is an infrequent benign liver tumor, which generally affects young women. It is asymptomatic, so its presentation is usually an imaging finding. Its management is expectant in most cases. The objective of this article is to present a clinical case whose presentation and resolution were atypical.